Register of patients with familial hypercholesterolemia and patients of very high cardiovascular risk with lipid-lowering therapy underperformance (RENESSANS) - M. V. Yezhov; S. A. Bliznyuk; N. A. Tmoyan; T. A. Rozhkova; D. V. Duplyakov; V. A. Salchenko; M. A. Kachkovsky; I. I. Shaposhnik; V. V. Genkel; V. S. Gurevich; S. А. Urazgildeeva; A. V. Tregubov; et al. (Российский кардиологический журнал, 2019)
Aim. Russian multicenter register of familial hypercholesterolemia (FH) was transformed into Register of patients with FH and very high cardiovascular risk with insufficient effect of hypolipidemic therapy (RENESSANS Registry) in 2017 The aim of RENESSANS was maximal inclusion of patients not only with FH, but also those with atherosclerotic cardiovascular diseases (CVD), who did not achieve targeted level of low density lipoprotein cholesterol (LDL-C) using hypolipidemic drug therapy.Material and methods. The RENESSANS Registry is an open, national, observing study that includes patients with definite and probable (according to Dutch lipid clinic network and Simon Broome Registry criteria) heterozygous and homozygous FH, as well as patients of very high cardiovascular risk. There were designed two register forms: for patients with FH and for very high cardiovascular risk patients. Doctors filled out forms in paper and electronic variants. They took into consideration the risk factors of atherosclerosis and anamnesis of CVD, adherence to diet and hypolipidemic therapy. Concentrations of total cholesterol (TC), triglycerides (TG), high density lipoprotein cholesterol (HDL-C) were measured in blood serum in all centers. LDL-C level was defined according to Friedewald formula: LDL-C=TC-HDL-C-TG/2,2 (mmol/l).Results. The Registry consisted of 1208 FH patients and 497 patients with very high risk (average age 54±13 and 61±8, respectively, 37% men). Baseline levels of lipids were 9,4±2,3 and 6,9±1,5 mmol/l for TC, 6,6±2,1 and 4,5±1,3 mmol/l for LDL-C, respectively. The frequency of hypolipidemic therapy in both groups is 70%, while targeted level of LDL-C was achieved extremely rarely.Conclusion. The results show insufficient adherence and low effectiveness of standard hypolipidemic therapy both in patients with FH and very high cardiovascular risk. PCSK9 inhibitors are recommended for resistant hypercholesterolemia treatment. The RENESSANS Registry allows to improve FH diagnostics, to assess treatment effectiveness and choose patients who need treatment with PCSK9 inhibitors.